2016
DOI: 10.4236/ojms.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of <i>Spirulina platensis</i> on Deltamethrin-Induced Biochemical Alterations and Oxidative Stress in the African Catfish; <i>Clarias gariepinus</i>

Abstract: The present study was carried out to determine LC 50 of deltamethrin (DM) in the African catfish; Clarias gariepinus, investigate its effects on the biochemical parameters and the antioxidant status of various tissues, and assess the protective role of Spirulina platensis (SP) against DM induced toxicity in C. gariepinus. The fish were distributed into seven groups of 10 fish/each for 30 days as follows: Group 1, control; Group 2, orally administered saline; Group 3, oral SP (150 mg/kg b.w.); Group 4, exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
5
6
0
1
Order By: Relevance
“…In the present study, lowest values of total protein, albumin, and globulin were observed in fish exposed to 3.28 µg BPA/L as compared with the control fish ( p < 0.05; Table ). These findings agreed with that recorded in African catfish after pesticide exposure (Hamed, ; Marzouk et al, ; Sayed & Hamed, ). The depletion of serum total protein, albumin, and globulin in the BPA‐exposed fish may be a result of dysfunctions of the liver and kidney (Girón‐Pérez et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, lowest values of total protein, albumin, and globulin were observed in fish exposed to 3.28 µg BPA/L as compared with the control fish ( p < 0.05; Table ). These findings agreed with that recorded in African catfish after pesticide exposure (Hamed, ; Marzouk et al, ; Sayed & Hamed, ). The depletion of serum total protein, albumin, and globulin in the BPA‐exposed fish may be a result of dysfunctions of the liver and kidney (Girón‐Pérez et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, elevated levels of serum AST, ALT, and ALP levels in BPA‐exposed animals compared to a control group were observed in rats (Ahmed, Moselhy, & Nabil, ; Korkmaz, Ahbab, Kolankaya, & Barlas, ) and fish (Hamed & Abdel‐Tawwab, ). Additionally, similar results were reported in activities of liver enzymes of African catfish upon exposure to 4‐NP (Sayed & Hamed, ; Sayed, Mekkawy, & Mahmoud, ) and deltamethrin (Hamed, ), respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Catfish exposed to BPA exhibited hypoproteinaemia, hypoalbuminaemia, and hypoglobulinaemia compared to the control ones. These results agreed with that documented in African catfish after pesticide exposures (Hamed, 2016;Marzouk et al, 2012;Sayed and Hamed, 2017;Abdel-Tawwab and Hamed, 2018). The depletion of serum total protein, albumin, and globulin in the BPA-exposed fish may be a result of dysfunctions of the liver and kidneys (Giron-Pérez et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…The SOD and CAT system, the first line of defense system against oxidants varied according to the response of fish antioxidant system to counteract with the toxicity of metal exposure [31]. The increase in SOD and CAT enzymes may be due to the elimination of ROS from the cell induced by exposure to pollutants which convert superoxide anions (O 2 -) into H 2 O 2 and then into H 2 O and O 2 [32]. GST plays an important role in homeostasis, detoxification and clearance of many xenobiotic compounds.…”
Section: Oxidative Stress Parametersmentioning
confidence: 99%